The monitored patient: Ethics and human rights in the development of medical technology Der überwachte Patient Ethik und Menschenrechte bei der Entwicklung von Medizintechnik - Frewer, Andreas; Schmidhuber, Martina (Zeitschrift für medizinische Ethik, 2016)
In the last decades medical technology has changed our society fundamentally. To begin with, this contribution traces the historical development of medical technology. The contribution then proceeds to describe which ethical aspects are to be taken into account in the context of surveillance technology. From »FitBits« to »Apps« for health control - technical innovations provide both chances and risks for the healthcare sector. It is necessary to maintain the right to informational self-determination, for which each individual also holds certain self-responsibility.
CRIS-Team Scopus Importer:2025-03-13
Keywords: history and ethics; Human Rights; infor mational self-determination; Monitoring of patients; technology in medicine